Don't look back in anger: A cross-sectional and dyadic examination of the Dark Triad, anger, and aggression in athletes. (January 2023) - Bryan, William; Donachie, Tracy C.; Vaughan, Robert S.; Madigan, Daniel J.
Abstract: Objectives: The Dark Triad (psychopathy, Machiavellianism, and narcissism) has been linked to anti-social behaviour in sport, and while anti-social behaviour often involves aggression and violence, no research to date has examined the relationship between the Dark Triad and anger and aggression in athletes. The current two-sample study sought to address this gap. Design: Multi-sample cross-sectional design. Method: Sample 1 included 224 athletes ( M AGE = 23.85) and Sample 2 included 98 coach-athlete dyads (196 total; athlete M AGE = 18.15, coaches M AGE = 34.84). In both samples, facets of the Dark Triad were related to anger and aggression. Results: In Sample 1, regression analyses indicated that psychopathy positively predicted both anger and aggression and Machiavellianism positively predicted aggression. In Sample 2, actor-partner interdependence models indicated a combination of dyadic relationships (i.e., both actor [coach and athlete personality predicted their own anger and aggression] and partner effects [coach and athlete personality predicted the other's anger and aggression]). In this regard, actor effects were found between psychopathy and both anger and aggression and narcissism and aggression. Coach to athlete partner effects were found for narcissism and anger and Machiavellianism and aggression. Conclusions: Overall, the findings provide evidence for personal and interpersonal relationships between the Dark Triad and anger and aggression and highlight the potential for the darker side of both athlete and coach personality to influence athlete emotions. Highlights: Research has yet to examine the relationship between the Dark Triad and aggression and anger in sport. Two samples of athletes and coaches completed self-report measures of the Dark Triad and aggression and anger. Regression showed that ppsychopathy predicted aggression and anger and Machiavellianism predicted aggression. Actor-partner independence models showed actor effects between psychopathy and both anger and aggression and narcissism and aggression. Results also indicated coach to athlete partner effects for narcissism and anger and Machiavellianism and aggression.